1983
DOI: 10.1126/science.6224294
|View full text |Cite
|
Sign up to set email alerts
|

Down's Syndrome in Adults: Brain Metabolism

Abstract: The cerebral metabolic rate for glucose, as measured with positron emission tomography and fluorine-18-labeled 2-deoxy-D-glucose, was significantly higher in four healthy young subjects with trisomy 21 syndrome (Down's syndrome) than the mean rate in healthy young controls. The rate of cerebral glucose utilization in the frontal lobe of a 51-year-old subject with Down's syndrome was significantly lower than the rate in the young subjects with this syndrome, but approximated the rate in middle-aged controls. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
22
0

Year Published

1984
1984
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(25 citation statements)
references
References 20 publications
3
22
0
Order By: Relevance
“…Global gray CMRglc equaled 8.76 ± 0.76 mg/IOO g/min (mean ± SD) in the DS group as compared with A previous study in our laboratory using positron emission tomography (PET) and eSp]2-fluoro-2-de oxy-D-glucose eSPDG) showed that Down syn drome (DS) adults over the age of 45 years have reductions in parietal and temporal glucose metab olism in comparison with younger DS adults (Scha piro et al, 1987b). However, another study in our laboratory did not find this pattern in four younger DS adults when compared with controls, although these young DS subjects had a mean global increase in glucose metabolism (Schwartz et al, 1983). Be cause this latter study used a calculated correction Gray matter regional measurements also did not differ between groups.…”
mentioning
confidence: 67%
See 2 more Smart Citations
“…Global gray CMRglc equaled 8.76 ± 0.76 mg/IOO g/min (mean ± SD) in the DS group as compared with A previous study in our laboratory using positron emission tomography (PET) and eSp]2-fluoro-2-de oxy-D-glucose eSPDG) showed that Down syn drome (DS) adults over the age of 45 years have reductions in parietal and temporal glucose metab olism in comparison with younger DS adults (Scha piro et al, 1987b). However, another study in our laboratory did not find this pattern in four younger DS adults when compared with controls, although these young DS subjects had a mean global increase in glucose metabolism (Schwartz et al, 1983). Be cause this latter study used a calculated correction Gray matter regional measurements also did not differ between groups.…”
mentioning
confidence: 67%
“…However, another study in our laboratory did not find this pattern in four younger DS adults when compared with controls, although these young DS subjects had a mean global increase in glucose metabolism (Schwartz et al, 1983). Be cause this latter study used a calculated correction 8.74 ± 1.19 mg/lOO g/min in the control group (p > 0.05).…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…The lower metabolic rate in the most skilled subjects was interpreted as indicating greater neural efficiency. Similarly, patients with Down's syndrome and other forms of mental retardation also show increased global metabolic activity (Cutler, 1986;Haier et al, in press;Schwartz et al, 1983). In the current study, well-educated and highly motivated subjects may have made more effort in executing the task during the second scan when the dementing process had progressed further.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Schwartz et al (1983) in our laboratory, using an ECAT II scanner (Ortec, Life Sciences, Oak Ridge, TN, U.S.A.) and a calculated attenuation correc tion algorithm, reported that regional CMRg 1 c (rCMRglc) was higher in young adult Down syn drome subjects than in controls. However, the dif ference lay not in the subjects but in the calculated attenuation correction, which S. Bacharach and M. Schapiro (unpublished observations) later demon strated overestimates rCMRglc in subjects with small heads, like Down syndrome subjects.…”
Section: A140mentioning
confidence: 99%